(untitled) (World Bulletin of Public Health, 2024)
In most countries of the world, pneumonia is defined as “an acute infectious disease of the pulmonary parenchyma, diagnosed by the syndrome of respiratory distress and/or physical findings, as well as infiltrative changes on the radiograph.” This definition assumes the diagnosis of pneumonia only in “X-ray positive” cases of lower respiratory tract infections. This approach allows us to exclude diseases such as bronchitis and bronchiolitis, which in most cases are viral and do not require antibacterial treatment.